Invasion, expansion, and control of Bactrocera dorsalis (Hendel) in China - Huan LIU; Dong-ju ZHANG; Yi-juan XU; Lei WANG; Dai-feng CHENG; Yi-xiang QI; Ling ZENG; Yongyue LU (Journal of Integrative Agriculture, 2019)
The Oriental fruit fly, Bactrocera dorsalis (Hendel), is among the most destructive fruit/vegetable-eating agricultural pests in the word, particularly in Asian countries such as China. Because of its widespread distribution, invasive ability, pest status, and economic losses to fruit and vegetable crops, this insect species is viewed as an organism warranting severe quarantine restrictions by many countries in the world. To understand the characteristics and potential for expansion of this pest, this article assembled current knowledge on the occurrence and comprehensive control of the Oriental fruit fly in China concerning the following key aspects: invasion and expansion process, biological and ecological characteristics, dynamic monitoring, chemical ecology, function of symbionts, mechanism of insecticide resistance, control index, and comprehensive control and countermeasures. Some suggestions for the further control and study of this pest are also proposed.